Low-Carbon Society Concept: Experience and Issues (Journal of Oriental Studies, 2017)
This article describes the reasons for creation of low-carbon society inJapan and its basic concept. The basic characteristics and key indicators ofthe concept have been considered. Two scenarios for developing a lowcarbonsociety in Japan by 2050 and its positive effects were analysed.In addition, the article shows the modern achievements of Japan in theimplementation of the low-carbon society concept.